MICROBIAL DEINKING OF PRINTED PAPER - ELAVARASI NATARAJAN, (International Journal of Pharma and Bio Sciences, 2014)
In this study we report the deinking of printed paper using microorganisms isolated from oil contaminated soil. The microorganisms producing lipase and esterase enzymes were screened using tributyrin agar. Deinking of the pulp was carried out using screened microorganisms and the preliminary identification of the microorganism that showed effective deinking was carried out by biochemical tests such as Gram straining ,TSI, MR-VP, Indole test, catalase test which indicated the presence of Pseudomonas sp. which was further confirmed by 16s-rRNA sequencing. The obtained sequence was analysed by bioinformatics tools which showed 98% sequence alignment with Pseudomonas aeruginosa. The microbially deinked pulp was subjected to SEM analysis to examine the fibre surface because an intact surface of individual fibres is desirable in paper making.